Undergraduate nursing students' experiences of palliative care in the intensive care unit - Pilaiporn Sukcharoen; Jidapa Polruk; Sununta Lukthitikul; Sadakan Eamchunprathip; Raphatphorn Petchsuk (BMC, 2023)
Abstract Background The terminal ill patients in the Intensive Care Unit had physical, mental, social, and spiritual suffering. Nursing students must be aware of own feelings to be able to deliver humanistic care and enable patients to live the rest of lives with dignity. The aim of the study was to investigate experiences of providing palliative care in the Intensive Care Unit (ICU). Method This study is a qualitative case study research. In-depth interviews were conducted with the key informants. The key informants were nine Thai third-year nursing students were purposively selected. Results The experiences of providing palliative care involved two Themes: (1) self-perception while providing care for terminal ill patients and (2) providing care for terminal ill patients with respect in the patients' dignity. Conclusion These results can be applied to create learning activities to promote nursing students' self-awareness and enable them to provide humanized care for terminal ill patients.